Plasmodium falciparum induces Foxp3hi CD4 T cells independent of surface PfEMP1 expression via small soluble parasite components - Scholzen, Anja; Cooke, Brian M.; Plebanski, Magdalena (Frontiers in Microbiology, 2014)
Elevated levels of regulatory T cells following Plasmodium infection are a well-reported phenomenon that can influence both protective and pathological anti-parasite responses, and might additionally impact on vaccine responses in acutely malaria infected individuals. The mechanisms underlying their induction or expansion by the parasite, however, are incompletely understood. In a previous study, Plasmodium falciparum infected red blood cells (iRBCs) were shown to induce effector-cytokine producing Foxp3int CD4+ T cells, as well as regulatory Foxp3hi CD4+ T cells in vitro. The aim of the present study was to determine the contribution of parasite components to the induction of Foxp3 expression in human CD4+ T cells. Using the surface PfEMP1-deficient parasite line 1G8, we demonstrate that induction of Foxp3hi and Foxp3int CD4+ T cells is independent of PfEMP1 expression on iRBCs. We further demonstrate that integrity of iRBCs is no requirement for the induction Foxp3 expression. Finally, transwell experiments showed that induction of Foxp3 expression, and specifically the generation of Foxp3hi as opposed to Foxp3int CD4 T cells, can be mediated by soluble parasite components smaller than 20nm and thus likely distinct from the malaria pigment hemozoin. These results suggest that the induction of Foxp3hi T cells by P. falciparum is largely independent of two key immune modulatory parasite components, and warrant future studies into the nature of the Foxp3hi inducing parasite components to potentially allow their exclusion from vaccine formulations.